“ And we love these little bracelets offered ” : Folkcommunication in the vaccination campaign against COVID - 19 i n Recife - PE (Revista Internacional de Folkcomunicação, 2021)
The present work seeks to point out forms of Folk political communication using appropriation of digital media by popular groups, focusing on informal communication processes. The objective is to verify how the City of Recife uses the social network to interact with readers-internet users on the progress with the vaccination against COVID-19 of the population of Recife. It is in the appropriation of elements of folk culture by mass culture that we find the use of social networks as a vehicle for political folk communication by the City of Recife. Folk political communication; pandemic; media.